Dimension manifestation of users’ psychographic traits towards online travel agency / Abdul Aziz Azdel... [et al.] - Azdel, Abdul Aziz; Awang, Khairil Wahidin; Raja Yusof, Raja Nerina; Mohd Radzi, Salleh; Ismail, Mohd Noor Ismawi (Universiti Teknologi MARA, Negeri Sembilan, 2019)
The purpose of this study is to assess the determinants of psychological traits towards users’ technology experience specifically on Online Travel Agencies (OTA) via exploratory factor analysis (EFA). Working on these issues and after sequences of analyses to verify reliability and factor structure, the final 16 items of Technology Readiness 2.0 (TR2.0) with 4 items for each dimension (Optimism, Innovativeness, Discomfort, and Insecurity) have been congregated. Through an online survey, the technology readiness determinants were administered to 100 travelers at KLIA2 who have experienced on OTA. EFA using Principal Component Analysis with Varimax Rotation indicated 14 items, with 4 factors final solution with the following subscales: Innovativeness (4 items); Optimism (4 items); Discomfort (3 items); and Insecurities (3 items). All in all, only two items were removed from the original total of 16 items by the factor analysis based on the factor loading matrix for this final solution. This study basically plays an important role in contributing to the existing literature on the OTA users’ standpoint by using an approach which is very powerful to redefine the factors within Technology Readiness. This enhancement has reorganized the items according to their importance specifically towards new perspective which are OTA users in Malaysia setting.